A Proposal for Dictionarization of an Indian Language - Soares, Marília (Meta, 1996)
AbstractThis article presents a proposal for a dictionary whose preparation relies partly on Indian knowledge. The Indians themselves would be active participants in this process for which the author has coined a term: dictionarization. The article concludes with a correlation between dictionarization and the translation of conceptual terms from an Indian language.